The Ideology within Covid-19 Public Service Advertisements: A Semiotic Approach - Sulatra, I Komang; Eka Pratiwi, Desak Putu (Humanis; Vol 24 No 4 (2020)DO - 10.24843/JH.2020.v24.i04.p02, 2020)
The COVID-19 virus is a new virus linked to the same family of viruses as Severe Acute Respiratory Syndrome (SARS). The virus is transmitted through direct contact with respiratory droplets of an infected person and touching surfaces contaminated with the virus. COVID-19 patients in Indonesia continue to grow. The Indonesian government has made efforts to break the chain of the spread of the COVID-19. One of them is by creating COVID-19 public service advertisements. Public service advertisement plays an important role in this pandemic to spread positivity which can motivate people to survive in this difficult time. This study aims at analyzing the ideology within COVID-19 public service advertisements by analyzing the meaning of verbal and visual signs used in those advertisements. The data were taken from five selected posters of COVID-19 public service advertisements. The data were collected by observation method and analyzed by qualitative method using theory of Semiotic proposed by Barthes (1998) and theory about ideology by Storey (2009). The analysis is presented in informal method. Our finding shows there are various ideologies used in COVID-19 public service advertisements, such as: prevention is better that cure, the ideology of being cooperative, responsible, productive and optimistic in facing COVID-19 pandemic. COVID-19 public service advertisements generally deliver a massage that together we can defeat COVID-19.